Neurodevelopment and Genetic Evaluation of Sotos Syndrome Cases with a Novel Mutation: a Single-Center Experience - Muhsin, Elmas; Basak, Gogus; Banu, Degirmenci; Alper, Gezdirici; Mustafa, Solak (Springernature, 2022)
Sotos syndrome is a non-progressive neurological disease with overgrowing, increased bone age, and developmental retardation. The aim of this study is to evaluate the prenatal, natal, and postnatal clinical findings of patients with Sotos syndrome. Sixteen patients suspected to have Sotos syndrome with clinical findings were examined retrospectively, ranging in ages between 3 and 23. In our file screening, we screened the FISH results of all 16 patients, but not all patients had NSD1 gene analysis results. We collected NSD1 gene analysis results, if there were any. The parameters that we investigated for these patients are birth weight, birth length, Apgar score at the 5th minute, dysmorphological face appearance, bone age, seizure, learning disability, feeding difficulties, surgical operation, and other accompanying abnormalities (brain MRI, abnormal echocardiographic findings, chronic otitis media, etc.). The anamnesis, clinical examination findings, and genetic reports of the patients were examined. For this, the hospital registration system was used. Breech presentation, Apgar score in the 5th minute of between 4 and 7, atrial septal defect at echocardiography, and consanguineous marriage rate were detected to be increased in individuals with Sotos syndrome compared to the normal population. When compared to the general population, delayed psychomotor development was determined. Macrocephaly, increased bone age, chronic otitis media frequency, and hernia operation frequency were determined to see if all patients were consistent with the literature. As a result of NSD1 gene sequencing analyses (NSD1 gene analysis was performed in 6 patients and a mutation was detected in 3 of them), three were found to have NSD1 gene mutation (one of them was novel). A novel deletion-type mutation that was not previously reported in the literature in the 19th exon of the NSD1 gene was determined. Xiphoidal protrusion was detected on this patient that had the novel mutation, and this situation has not been reported in the literature previously. If a patient has rapid growth, difficulty in learning, macrocephaly, speech delay, and timid personality, Sotos syndrome can be considered at the pre-diagnosis stage.
Keywords: Sotos syndrome; Macrocephaly; Fetal macrosomia